Lived experiences of parentally bereaved adolescents due to Super Typhoon Yolanda - Bajamunde, Patrick Vense; Medalla, Elaine; Montances, Virly Rose; Negros, Maria Venus (2015)
This qualitative study aims to contribute to the existing body of literature regarding parentally bereaved adolescents. Parental death can be one of the most traumatic events that a child or adolescent can ever experience in life. The grief proces negatively affects every aspect of life; psychologically, socially, academically, physically and emotionally wherein changes in such aspects were manifested in the adolescents' daily life activities and personal well-being. The researchers in this study explored and analyzed the lived experiences of six (one male and five females) adolescents who lost one or both of their parents during the onslaught of the Super Typhoon Yolanda last November 2013. The adolescents lived in certain places in Tacloban City before the disaster and were relocated to different places in the same city particularly in bunkhouses after the Super Typhoon Yolanda destroyed their homes. The adolescents were selected through purposive and snowball sampling. Data were gathered using a semi-structured interview and were analyzed using thematic analysis method and Transitional Events Model. Results showed that the emotional, financial, academic, and social aspects in adolescents were found to be where their experiences of difficulties lie. Such lived experiences were less a consequence of bereavement as they are more a consequence of what happened to the family after their disaster and bereavement experience such as the relocation of the family which basically contributed to financial constraints faced by the family.